Cyclic high temperature corrosion studies of carbon nanotubes-Cr2O3 composite coatings on boiler steel at 900°C in molten salt environment. Issue 6 (20th September 2018) - Goyal, Khushdeep; Singh, Hazoor; Bhatia, Rakesh
Abstract : Purpose: Molten sulphate-vanadate induced hot corrosion is the main reason of failure of boiler tubes used at high temperatures in thermal power plants. The hot corrosion can be encountered by applying thermal spray coatings on the alloy steels. In this perspective, this paper aims to attempt to investigate the effect of carbon nanotubes reinforcement on Cr2 O3 composite coatings on hot corrosion behaviour of ASTM-SA213-T22 steel in a corrosive environment of Na2 SO4 – 60%V2 O5 at 900 ° C for 50 cycles. Design/methodology/approach: The coatings have been deposited with high velocity oxy fuel process. The samples were exposed to hot corrosion in a Silicon tube furnace at 900 ° C for 50 cycles. The kinetics of corrosion behaviour were analysed by the weight gain measurements after each cycle. Corrosion products were analysed with X-ray diffraction, scanning electron microscopy, energy dispersive and cross-sectional analysis techniques. Findings: During investigations, the carbon nanotubes (CNT) reinforced Cr2 O3 composite coatings on T22 steel were found to provide better corrosion resistance in the molten salt environment at 900 ° C. The coatings showed lower weight gain along with formation of protective oxide scales during the experiment. Improvement in protection against hot corrosion was observed with increase in CNT content in the coating matrix. Research limitations/implications: The addition of CNT has resulted in reduction in porosity by filling the voids in chromium oxide coating, with interlocking of particle and has blocked the penetration of corroding species to enhance the corrosion resistance of the composite coatings. The corrosion rate was found to be decreasing with increase in CNT content in coating matrix. Originality/value: It must be mentioned here that high temperature corrosion behaviour of thermally sprayed CNT-Cr2 O3 composite coatings has never been studied, and it is not available in the literature. Hence, present investigation can provide valuable information for application of CNT-reinforced coatings in high temperature fuel combustion environments.